2018
DOI: 10.1088/1361-665x/aaed4f
|View full text |Cite
|
Sign up to set email alerts
|

Untethered soft robotic jellyfish

Abstract: Inspired by natural creatures, soft robots possess the unique advantages of large actuation and excellent adaptability. Untethered designs of soft robots are drawing more attention to researchers, but current research is limited. Also, there is an increasing need to improve the performance of bio-mimetic robots. This work describes an untethered soft robotic jellyfish with high mobility that can mimic a natural jellyfish’s performance. The electrode of the robotic jellyfish is made by sandwiching carbon grease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…The ability to utilize the fluidic flow to achieve multiple functions and tasks is independent of the magnetic field since the incurred flow structures only rely on the interplay between the robot body and the fluid. Therefore, the above design and swimming modes may potentially be realized by current or future jellyfish-like soft robots built with other on-board or off-board actuation methods 48 such as biological muscle cells 30 , shape memory alloys 5 , hydraulic actuators 1 , dielectric elastomers 2,49 , hydrogels 50 , and liquid crystal elastomers 51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to utilize the fluidic flow to achieve multiple functions and tasks is independent of the magnetic field since the incurred flow structures only rely on the interplay between the robot body and the fluid. Therefore, the above design and swimming modes may potentially be realized by current or future jellyfish-like soft robots built with other on-board or off-board actuation methods 48 such as biological muscle cells 30 , shape memory alloys 5 , hydraulic actuators 1 , dielectric elastomers 2,49 , hydrogels 50 , and liquid crystal elastomers 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by ephyra, we propose an untethered jellyfish-like soft millirobot, which could realize multiple functionalities by producing diverse controlled fluidic flows around its body using its lappets, which are actuated by magnetic composite elastomer and bent by remote magnetic fields. Using this experimental setup, we study five distinct swimming modes to particularly investigate the interaction between the robot’s soft body and incurred fluidic flows due to the robot’s body motion and utilize such physical interaction for predation-inspired object manipulation capability of the robot, in addition to the robot’s swimming propulsion, which has been the only focus of previous jellyfish-like robot studies 1,2,5,30 . The proposed soft robot’s different lappet motion kinematics are used to conduct four different robotic tasks: selectively trap and transport objects of two different sizes, burrow into granular media consisting of fine beads to either camouflage or search a target object, enhance the local mixing of two different chemicals, and generate a desired concentrated chemical path.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work demonstrated the ability to effectively swim and transport cargo, but required an external field for propulsion. Recently, Cheng et al demonstrated an untethered soft robotic jellyfish that was powered by dielectric elastomer actuators (DEAs) that swam with a maximum speed of 1 cm s −1 (Cheng et al, 2019 ). While the work of Cheng et al was the first demonstration of an untethered jellyfish-inspired robot powered by DEAs, their work relies upon a prestretched membrane and hydrogel electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…19 Example of a bimorph bending DEA with oriented carbon fibers to constrain the defor-mation along predefined directions and therefore generate different actions (courtesy from Prof. David Clarke, Harvard University, USA) However, in this case, one of the two compliant electrodes required for actuation was replaced by the surrounding (conductive) water and the control electronics was embedded on board, obtaining an untethered (i.e., fully autonomous) robot. Plastic extensions were added to increase the thrust force (Cheng et al 2019).…”
Section: Robotic Jellyfishesmentioning
confidence: 99%